2007
DOI: 10.1128/aac.01432-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Phosphorylation of 4′-Ethynyl 2′,3′-Dihydro-3′-Deoxythymidine with That of Other Anti-Human Immunodeficiency Virus Thymidine Analogs

Abstract: Thymidine analogs, including 3-azido-3-deoxythymidine (AZT) and 2,3-dideoxy-3-deoxythymidine (D4T), are important antiretroviral agents. To exert antiretroviral activity, these analogs undergo a stepwise phosphorylation intracellularly to the active triphosphate metabolites. We previously reported that 4-substituted D4T with an ethynyl group (i.e., 4-ethynyl D4T) increased the anti-human immunodeficiency virus (HIV) activity and was active against multidrug-resistant HIV strains. 4-Ethynyl D4T is a better subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…We also observed variability in the phosphorylation of different thymidine analogs (AZT and 4Ј-Ed4T) in some individuals. This may be due to the fact that the substrate specificity of the kinases at each phosphorylation step may be different or that more than one enzyme may be responsible for phosphorylation at each step (24,39). Turriziani et al also observed individual variability in TK-1 activity, though the variability was more marked in HIV-infected individuals than in healthy individuals (45).…”
Section: Downloaded Frommentioning
confidence: 90%
See 1 more Smart Citation
“…We also observed variability in the phosphorylation of different thymidine analogs (AZT and 4Ј-Ed4T) in some individuals. This may be due to the fact that the substrate specificity of the kinases at each phosphorylation step may be different or that more than one enzyme may be responsible for phosphorylation at each step (24,39). Turriziani et al also observed individual variability in TK-1 activity, though the variability was more marked in HIV-infected individuals than in healthy individuals (45).…”
Section: Downloaded Frommentioning
confidence: 90%
“…Phopshoglyceral kinase (PGK) can phosphorylate the diphosphate metabolites of nucleoside analogs such as AZT and ethynlystavudine (4Ј-Ed4T), a novel inhibitor, to their triphosphate metabolites (24). NRTI triphosphate is incorporated into HIV DNA by HIV reverse transcriptase (RT) and causes termination of HIV DNA chain elongation (27).…”
mentioning
confidence: 99%
“…Stepwise phosphorylation of festinavir occurs via the same enzymes as stavudine. Thymidine kinase 1 phosphorylates festinavir to festinavir-MP with 4-fold greater efficiency than stavudine (Hsu et al, 2007). The efficiency of festinavir-MP phosphorylation by thymidinylate monophosphate kinase is approximately 10 % of that seen for stavudine-MP or zidovudine-MP.…”
Section: Festinavirmentioning
confidence: 71%
“…The efficiency of festinavir-MP phosphorylation by thymidinylate monophosphate kinase is approximately 10 % of that seen for stavudine-MP or zidovudine-MP. Conversion from festinavir-DP to festinavir-TP appears to be catalyzed by multiple enzymes including nucleoside diphosphate kinase, pyruvate kinase, creatine kinase, and 3-phosphoglycerate kinase (Hsu et al, 2007). In contrast to other thymidine analogs which are readily catabolized by thymidine phosphorylase, festinavir catabolism cannot be detected.…”
Section: Festinavirmentioning
confidence: 90%
“…65 Nucleoside diphosphate kinase and 3'phosphoglycerate kinase converts ZDV-DP to the triphosphate form and 3'phosphoglycerate kinase converts 3TC-DP to the triphosphate form. 66 The main dephosphorylation enzymes are 5'nucleotidases, which oppose the first phosphorylation step and convert monophosphates back to the parent drug. 67 Phosphotases are broad-spectrum dephosphorylation enzymes that can also dephosphorylate drug-phosphates to the parent drug.…”
Section: Clinical Pharmacokineticsmentioning
confidence: 99%